A 40-Year-Old Woman With Grade Ii Hypertension and Obesity Case Report - Sulastri, Sulastri (CV. Publikasi Indonesia, 2025)
Hypertension is a global problem and its incidence continues to increase throughout the world, including in Indonesia. Hypertension is known as the silent killer because sufferers often do not show complaints or symptoms. Many people only find out that they have hypertension after complications. The incidence of hypertension is influenced by several risk factors. Modifiable risk factors of hypertension include diet, lack of physical activity, and overweight or obese. Management of hypertension not only focuses on pharmacology but also non-pharmacological therapy- life intervention, namely lifestyle changes and improving modifiable risk factors. Early management of hypertension is very important because it can prevent complications in several organs of the body such as the heart, kidneys, and brain.